2003
DOI: 10.1038/sj.ejhg.5201088
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and parental origin of de novo APC mutations in familial adenomatous polyposis

Abstract: A predominance of de novo mutations in the paternal germ line has been reported for several disorders; however, in familial adenomatous polyposis (FAP), the parental origin of APC mutations has been scarcely analysed so far. Among 563 unrelated FAP families with known family history, we identified 58 patients with a suspected de novo mutation in the APC gene. A germline mutation was detected in 52 of them; in 38 patients, the mutation could be excluded in both parents. The five base pair deletion at codon 1309… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(99 citation statements)
references
References 38 publications
(29 reference statements)
4
91
0
3
Order By: Relevance
“…Knowledge of haplotype structure is critical for understanding allele-specific events, such as methylation, that are cis-regulated (Tycko 2010), and it can provide valuable validation data for the study of population genetics (Conrad et al 2006) and genetic ancestry (Green et al 2010). The haplotype structure of an individual's genome is also essential for predicting instances of compound heterozygosity (McLaughlin et al 2010;Ng et al 2010) or for identifying the parental origins of de novo mutations (Glaser et al 2000;Aretz et al 2004).…”
mentioning
confidence: 99%
“…Knowledge of haplotype structure is critical for understanding allele-specific events, such as methylation, that are cis-regulated (Tycko 2010), and it can provide valuable validation data for the study of population genetics (Conrad et al 2006) and genetic ancestry (Green et al 2010). The haplotype structure of an individual's genome is also essential for predicting instances of compound heterozygosity (McLaughlin et al 2010;Ng et al 2010) or for identifying the parental origins of de novo mutations (Glaser et al 2000;Aretz et al 2004).…”
mentioning
confidence: 99%
“…Recent studies indicated the presence of mosaicism in approximately 15% of parents of apparently sporadic cases 7, 8.…”
Section: Case Reportmentioning
confidence: 99%
“…1, 2 • De novo events: 10-40%. 1, 3,4 • Broad spectrum of point mutations, 490% are truncating (nonsense, del/ins, splice sites). 2 • Mutational hot spots: c.3927_3931delAAAGA;p.(Glu1309Aspfs*4) (11%), c.3183_3187delACAAA; p.(Gln1062*) (7%), c.637C4T;p. (Arg213*) (3%), c.3202_3205delTCAA;p.(Ser1068Glyfs*57) (2%).…”
Section: Mutational Spectrummentioning
confidence: 99%